The Graft Infusion Technique (GIT) for Treatment of Peri-Implantitis Defects: Case Series - Bhatavadekar, Neel B; Gharpure, Amit S (Journal of dentistry (Shiraz), 2021)
Peri-implantitis is a site-specific infectious disease that causes an inflammatory process in soft tissues, and bone loss around an osseointegrated implant in function. Several techniques with non-surgical or surgical debridement and decontamination followed by ongoing supportive therapy or regeneration of the peri-implant bone defects have been proposed in the literature. However, the literature is still unclear on an effective protocol for implant surface decontamination or the appropriate choice of regenerative materials. This case series describes a surgical technique to treat peri-implantitis osseous defects using a mixture of deproteinized bovine bone mineral with 10% porcine collagen (DBBM-C) in a block form, soaked in an appropriate antibiotic. The use of this combination provides advantages such as good graft adaptability along with localized antibiotic release without the use of systemic antibiotics. Thus, this technique might be an effective method to treat amenable peri-implantitis defects. Additionally, the proposed algorithm also allows for customized culture based antibiotic loading. To the best of the authors' knowledge, this is the first case series documenting this technique for peri-implantitis defects. Long-term studies with controlled samples would be necessary for further evaluation.